Case report: Exotropia in waardenburg syndrome with novel variations - Huang, Lijuan; Guo, Maosheng; Li, Ningdong (Frontiers in Genetics, 2022)
Background: Waardenburg syndrome (WS) is a rare genetic disorder characterized by congenital sensorineural hearing loss and pigmentary abnormalities of the hair, skin and eyes. However, exotropia is rarely reported. The purpose of this study is to describe the clinical characteristics of three sporadic patients with WS and congenital exotropia and to investigate the disease-causing genes for them. Methods: Patients underwent detailed physical and ocular examinations. Ocular alignment and binocular status were evaluated. DNA was extracted and whole exome sequencing was performed to detect the pathogenic variations in the disease-causing genes for WS. Cloning sequencing was carried out for those indel variations. Results: Three unrelated patients were diagnosed with Waardenburg syndrome and congenital exotropia. Four novel variants, including c.136delA (p.I46Sfs*64) and c.668G>T (p.R223L) in PAX3, c.709dupC (p.Q237Pfs*119) in COL11A2, c.426G>A (p.W142X) in SOX10 gene, were detected in this study. Conclusions: Simultaneous presence of congenital exotropia and WS in our patients is suggested that WS could be involved in malfunction in the multiple nerve systems. Our genetic study will expand the mutation spectrum of PAX3, COL11A2 and SOX10 genes, and is helpful for further study on the molecular pathogenesis of WS.